2012
DOI: 10.1158/1940-6207.capr-11-0369
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Marker Changes in a Yearlong Randomized Exercise Intervention Trial among Postmenopausal Women

Abstract: Chronic low-grade inflammation is a possible risk factor for cancer that may be modifiable with long-term exercise. Very few randomized controlled trials (RCT) have studied the isolated effects of exercise on lowgrade inflammation exclusively in postmenopausal women. The Alberta Physical Activity and Breast Cancer Prevention Trial, a 2-armed RCT in healthy postmenopausal women, examined how 1 year of moderate to vigorous aerobic exercise, compared with usual inactivity, influenced circulating inflammatory mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 47 publications
2
63
0
3
Order By: Relevance
“…In our previous RCT, the Alberta Physical Activity and Breast Cancer Prevention (ALPHA) Trial, we demonstrated that a oneyear aerobic exercise intervention (prescribed 225 minutes/week) decreased circulating CRP, IL6, and TNFa levels compared with a usual inactive lifestyles defined as less than 90 minutes per week of physical activity (22). In an exploratory analysis, we also found that increasing exercise volume was associated with statistically significant linear trends of decreasing levels of these inflammatory markers.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…In our previous RCT, the Alberta Physical Activity and Breast Cancer Prevention (ALPHA) Trial, we demonstrated that a oneyear aerobic exercise intervention (prescribed 225 minutes/week) decreased circulating CRP, IL6, and TNFa levels compared with a usual inactive lifestyles defined as less than 90 minutes per week of physical activity (22). In an exploratory analysis, we also found that increasing exercise volume was associated with statistically significant linear trends of decreasing levels of these inflammatory markers.…”
Section: Introductionmentioning
confidence: 61%
“…The DREW trial found no direct effect of any amount of exercise on levels of CRP, IL6, of TNFa (40)(41)(42). However, three previous RCTs of exercise interventions in postmenopausal women found that an exercise or exercise and diet intervention significantly reduced levels of CRP compared with nonexercise controls: this effect was predominantly mediated by changes in adiposity (20)(21)(22). Baseline BMI was a moderator in one study as the effectiveness of the exercise intervention was only evident in obese women (BMI > 30 kg/m 2 ) at baseline (21).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on Kern et al's study (29), we can speculate that the exercise intervention favorably altered TNF-α expression, although significant changes required greater body fat loss than we observed in our study. It should be noted that in some similar RCTs, non-significant changes in the IL-6 level were reported (25,30,31), Thus, further studies are required to investigate local changes in TNF-α and IL-6 in postmenopausal women.…”
Section: Discussionmentioning
confidence: 96%